Live-bed failure modes of bendway weirs and rock vanes in alluvial channels - Maddocks, Parker, author; Ettema, Robert, advisor; Thornton, Christopher, advisor; Wohl, Ellen, committee member (Colorado State University. Libraries, 2022)
Bendway weirs and rock vanes have been used and refined for decades to control thalweg location and alignment along alluvial channel-bends and decrease flow velocity along the outer bank of such channels. Since the early 2000s, Colorado State University's Hydraulics Lab has assisted the U.S. Bureau of Reclamation (USBR) in refining design guidelines for bendway weirs, rock vanes, and other in-stream rock structures. This effort has entailed optimizing the layout of configurations of bendway weirs and rock vanes. The present study, however, focuses on the failure modes of bendway weirs and rock vanes, and led to the development of refinements to the design recommendations for individual bendway weirs and rock vanes so that such structures can perform as intended, even though the structures have encountered scour. Live-bed conditions were selected for the experiments, as such conditions involve active bed-sediment transport and, thereby, pose more severe conditions than do clear-water conditions in which little bed-sediment transport occurs. To investigate live-bed failure modes at bendway weirs and rock vanes, two flumes were used: a straight flume and a curved flume. The experiments used different parameters suggested in technical literature as documents as affecting bendway-weir and rock-vane performance (e.g., structure geometry, spacing, flow condition, and angle relative to a channel's outer bank). The straight flume was chosen for its capacity to create the constrained flow conditions needed to illuminate the failure modes, which then were verified using the curved flume, which was wider and subject to the effects of flow curvature. Each experiment involved a series of three bendway weirs or rock vanes. Preliminary experiments indicated that three structures were needed, because of observed differences in the failure modes at the three structures in a series. Experimental results revealed that failure modes of bendway weirs and rock vanes were primarily driven by rock dislodgement due to contraction scour at the tip of such structures, and by dune-trough presence at the upstream face (the first rock structure) and flow impingement (against the second rock structure). Also, flow swept some rock from the crest of bendway weirs and rock vanes. The observed failure modes in the straight flume were confirmed by the experiments using the curved flume, though the curved flume's curvature of flow and greater width partially obscured the failure modes. The failure modes led to refinements regarding the design recommendations for the structure of bendway weirs and rock vanes. The recommendations essentially specify the widening and lengthening of the crest of bendway weirs and rock vanes, so that these rock structures may experience controlled failure to accommodate scour but preserve their main dimensions.
Keywords: bendway weir; rock vane; failure modes; alluvial channels